Notas corológicas del macrofitobentos de Andalucía (España). XII. - Bermejo, Ricardo; Pérez-Lloréns, J. Lucas; Vergara, Juan J.; Hernández, Ignacio (Acta Botanica Malacitana, 2014)
New records for the macrophytobenthos of Andalusia (Spain). XII Palabras clave. Andalucía, corología, macroalgas marinas. Key words. Andalusia, geographical distribution, seaweeds.